Clinical Characteristics And Success Of Ptosis Surgery At Indonesia National Eye Center Cicendo Eye Hospital During January 2016 – December 2020 - Widhyasti, Rahayu; Boesoirie, Shanti Fitrianti (Universitas Malahayati, 2024)
Introduction: Ptosis is defined as drooping of the upper eyelid. Unilateral or bilateral ptosis can affect appearance and visual function, both of which can negatively impact quality of life. It may be congenital or acquired, determined by the timing of onset.Purpose: To describe clinical characteristics and surgical outcomse in ptosis correction surgery at Indonesia National Eye Centre, Cicendo Eye Hospital.Methods: This is a descriptive-retrospective study, medical records of patients who was admitted to Indonesia National Eye Centre, Cicendo Eye Hospital, from January 2016 to December 2020 with diagnosis of eyelid ptosis were included in this study.Results: From total of 189 patients (209 eyes) in this study, there were 41,8% male and 58,2% female patients with median age 22 years at the first time of visit. Most of the patients had unilateral ptosis (89,5%), and 10,5% had unilateral ptosis. According to the etiology of ptosis, 34,2% eyes were neurogenic ptosis. Degree of ptosis were severe in 70,9% eyes and most patients had fair levator function. Success rate were more than 95% in ptosis patient who underwent surgery.Conclusion: Majority of ptosis patient in Indonesia National Eye Centre, Cicendo Eye Hospital were caused by neurogenic followed by mechanical, traumatic, aponeurotic, myogenic, and pseudoptosis. Female patients were more common than male patients and median age at the first time visit were during second decade of life. Surgical outcome in ptosis tend to have high clinical success rates.Keywords: Characteristic; Outcome; Ptosis; Surgery